2002
DOI: 10.1161/01.hyp.0000018910.74377.93
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effect of Chronic Adrenomedullin Infusion in Dahl Salt-Sensitive Rats

Abstract: Abstract-The present study was designed to examine whether chronic adrenomedullin infusion has renoprotective effects in hypertensive renal failure and the mechanism by which chronic adrenomedullin infusion exerts its effects. Dahl salt-sensitive rats and Dahl salt-resistant rats were fed a high salt diet starting at 6 weeks of age. Recombinant human adrenomedullin or vehicle was infused for 7 weeks in 11-week-old Dahl salt-sensitive rats. Dahl salt-resistant rat was used as a control. After 7 weeks, untreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…The investigators themselves pointed out that the frequency of the 19-repeat allele of the microsatellite was not increased in hypertensive diabetic patients without nephropathy, which decreases the likelihood that the relationship between the 19-repeat allele and diabetic nephropathy is mediated by a predisposition to hypertension. AM has been reported to play a renoprotective role in chronic hypertensive renal failure (28), and the plasma and urinary AM levels in patients with chronic glomerulonephritis have been shown to reflect the disease activity or glomerular damage represented by the degree of PU (29). Overall these results suggest that AM is involved in the pathophysiology of renal function or PU.…”
Section: Discussionmentioning
confidence: 75%
“…The investigators themselves pointed out that the frequency of the 19-repeat allele of the microsatellite was not increased in hypertensive diabetic patients without nephropathy, which decreases the likelihood that the relationship between the 19-repeat allele and diabetic nephropathy is mediated by a predisposition to hypertension. AM has been reported to play a renoprotective role in chronic hypertensive renal failure (28), and the plasma and urinary AM levels in patients with chronic glomerulonephritis have been shown to reflect the disease activity or glomerular damage represented by the degree of PU (29). Overall these results suggest that AM is involved in the pathophysiology of renal function or PU.…”
Section: Discussionmentioning
confidence: 75%
“…However, recent studies suggest that treatment with Ang I-converting enzyme inhibitors or Ang II type I receptor antagonists reduces cardiac and/or renal dysfunction in DS rats made hypertensive by a HS diet. [5][6][7][8][9][10] Furthermore, Nakaya et al 15 reported that prepubertal treatment with an Ang II type I receptor antagonist causes partial attenuation of hypertension and ameliorates the renal damage in adult DS rats fed HS. These data suggest that the local RAS may contribute to development of hypertension and renal dysfunction in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Although generally considered to be characterized by a low activity of circulating RAS, recent studies indicate that treatment with angiotensin (Ang) I-converting enzyme inhibitors or Ang II type I receptor antagonists reduces cardiac and/or renal dysfunction in DS rat fed a high salt diet (HS). [5][6][7][8][9][10] These findings suggest that the local RAS may be inappropriately activated and contribute to the development of hypertension in this animal model.Previous studies have demonstrated that Ang II infusions to normal rats result in paradoxical increases in renal expression of AGT mRNA 11,12 and protein. 13 Furthermore, urinary excretion of AGT was significantly increased in Ang II-infused rats, which was associated with an enhancement of intrarenal Ang II levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings showed that AM gene delivery attenuates hypertension, protects against cardiac remodeling and renal damage in hypertension, and may have significance in therapeutic applications in cardiovascular and renal diseases. We also recently reported that chronic human AM infusion exerted renoprotective effects in a rat model of malignant hypertension (48,49). Human AM infusion significantly reduced plasma renin concentration, plasma aldosterone levels and plasma endogenous rat AM levels with a slight increase of plasma human AM levels.…”
Section: Chronic Administration Of Am In Heart Failurementioning
confidence: 88%